Paternity Dalam Perspektif Hukum Islam Pada Negara-Negara Muslim Di Dunia - Adji Pratama Putra; Fajri Romadhon (Sanskara Hukum dan HAM, 2023)
This research examines the legitimacy of children, child custody, and child guardianship in the perspective of Islamic law in Muslim countries in the world. This study aims to find out how the implementation of child legitimacy, child custody, and child guardianship in the perspective of Islamic law exists in Muslim countries in the world. This study uses library research by collecting qualitative data. Data is obtained by collecting from several sources, such as books and journal articles. The approach in this research is normative by analyzing existing rules in several countries related to child legitimacy, child custody, and child guardianship that already exist and are clearly described. The results of this study indicate that child legitimacy, child custody, and child guardianship have different provisions and are regulated in different laws in every Muslim country in the world.